OPTIMAL CONTROL OF INVESTMENTS IN A DYNAMIC MODELS OF DUOPOLY - Y. Aganin (Вестник университета, 2017)
The paper studies profit maximization in three dynamic models of duopoly. The first one describes the dynamics of production and capital-labor ratio with equilibrium price, the second - the same problem with non-equilibrium price and the third one analyzes the optimal external financing of capital expenditures and working capital.